Pre-service Arabic Language teachers’ readiness in Digital Media Based on European Profiling Grid - Fatwa Arifah; Raden Ahmad Barnabas; Siti Maryam (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2022)
This study measures the readiness of Pre-service Arabic teachers to digital media based on the European Profiling Grid (EPG). Using the descriptive qualitative method, this study took data from 57 students of the Arabic Education Study Program. The results describe 98% was in the first development stage which is: can download resources from websites. While the lowest readiness with a percentage of 16% is in the third stage with indicators: can design blended learning modules using a learning management system. Therefore, it can be concluded that Pre-service Arabic teachers have a high readiness to use and implement digital media in teaching the Arabic language. However, there needs to be an effort to increase their readiness to use and implement the Learning Management System in their teaching practice. In addition, the results of this study are expected to be useful for mapping the stages of readiness of Pre-service Arabic language teachers to digital media, so that Pre-service Arabic language teachers know their strengths and weaknesses in utilizing digital media in their teaching, and it can also motivate them to develop their potential especially in the use of the digital media.